Ethnomedicinal bioprospecting of Rhizophora apiculata leaves through in silico and in vitro approaches as antioxidant, ?-glucosidase inhibitor and anticancer - MADA TRIANDALA SIBERO; RUDHI PRIBADI; AMBARIYANTO AMBARIYANTO; DWI HARYANTI; VIOL DHEA KHARISMA; ARIYANTI S. DEWI; GINTUNG PATANTIS PATANTIS; DEWI S. ZILDA; RETNO MURWANI (Society for Indonesian Biodiversity, 2022)
Abstract. Sibero MT, Pribadi R, Ambariyanto A, Haryanti D, Kharisma VD, Dewi AS, Patantis G, Zilda DS, Murwani R. 2022. Ethnomedicinal bioprospecting of Rhizophora apiculata leaves through in silico and in vitro approaches as antioxidant, a-glucosidase inhibitor and anticancer. Biodiversitas 23: 6437-6447. Investigating marine natural products for biopharmaceutical development leads to a massive study of mangrove metabolites. Rhizophora apiculata is utilized as a traditional medicine by the local community in Indonesia. However, only a few studies reported the lead compounds. The aim of this study was to discover the biological properties of R. apiculata metabolites from the leaves as an antioxidant, a-glucosidase inhibitor, and anticancer agent through in vitro and in silico approaches. The leaves of R. apiculata were extracted and then fractionated using the silica-OCC method. All fractions were screened for antioxidant, a-glucosidase inhibitors, and cytotoxicity assays. Then the bioactive compounds in prospective fractions were identified using LC-HRMS. The selected compounds with ppm error <10 were applied for in silico analysis. The result of biological properties screening indicated Fr. 5 and Fr. 6 as the most potent sources of antioxidants, a-glucosidase inhibitors, and cytotoxic compounds. In total, 19 compounds were selected from two prospective fractions. The drug-likeness and bioavailability prediction results indicated that all selected compounds act as drug-like molecules. In addition, 17 were predicted to have antioxidant activity, and 15 compounds had antidiabetic activity. Moreover, 15 compounds had a more negative affinity binding than cytarabine. Molecular docking analysis showed that the mechanism of cytotoxicity against P388 Murine Leukaemia Cells was through the interaction of apigenin with protein tyrosine kinase (c-Kit) with a stronger inhibitory activity than the control drug (Cytarabine) and had the same binding site as the control (Cytarabine).